Kesiapsiagaan Perpustakaan Dalam Menghadapi Bencana Kebakaran di Dinas Perpustakaan Dan Arsip Daerah Provinsi Jambi - Pitri, Novita (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2019)
Introduction. The purpose of this study is to find out how library preparedness in facing fire disasters in the Regional Library and Archives Service of Jambi Province, what are the factors that hamper the library to make preparedness in facing fire disasters and what are the supporting factors to overcome obstacles to library preparedness in facing fire disasters at the Jambi Provincial Library and Archives Service. Data collection method. This research is a qualitative research with a descriptive approach with data collection techniques used, namely interviews, observation and documentation. The subjects of this study were the Head of the Library, the Secretary, the Librarian, the Head of the Kasubbid Program for the Preservation of Library Materials and the Fire Service Officer and firefighters. The sampling technique used in this study is purposive sampling to determine the sampling with characters in accordance with the objectives of the study. Analysis data. The data analysis techniques used are data reduction analysis, data presentation and conclusions. Result and Discussion. The results of this study that preparedness in the face of fire disaster Jambi Provincial Library and Archive Service at the prevention stage are routine inspections of buildings, routine inspections of fire fighting equipment, marking and securing very important collections, not providing training to staff, not insuring buildings and collection and has conducted a fire disaster risk analysis. At the planning stage, which has not made guidelines and policies for fire disaster management, has not selected and determined staff members of the fire disaster management team, identified and secured collections that are important and rare, has not made a list containing the names of experts, consultants and institutions authorities, both government and private, must be contacted immediately in the event of a fire disaster and have not renewed and regularly checked insurance agreements. The factors that hamper Jambi Province to prepare in the face of a fire disaster are the budget, human resources and fire fighting equipment. Supporting factors to overcome the obstacle of library preparedness in facing fire disaster in the Jambi Provincial Library and Archives Service is to utilize the existing budget. Conclusions. There are two stages of the library in disaster preparedness, namely, the prevention and planning stages. It is hoped that the library can maximize the implementation of fire disaster preparedness, especially at the prevention and planning stages.